Signalling through Src family kinase isoforms is not redundant in models of thrombo‐inflammatory vascular disease. Issue 9 (4th July 2018) - Harrison, Matthew J.; Chimen, Myriam; Hussain, Mohammed; Iqbal, Asif J.; Senis, Yotis A.; Nash, Gerard B.; Watson, Steve P.; Rainger, G. Ed
Abstract: The Src family kinases (SFK) are a group of signalling molecules with important regulatory functions in inflammation and haemostasis. Leucocytes and platelets express multiple isoforms of the SFKs. Previous studies used broad‐spectrum pharmacological inhibitors, or murine models deficient in multiple SFK isoforms, to demonstrate the functional consequences of deficiencies in SFK signalling. Here, we hypothesized that individual SFK operate in a non‐redundant fashion in the thrombo‐inflammatory recruitment of monocyte during atherosclerosis. Using in vitro adhesion assays and single SFK knockout mice crossed with the ApoE −/− model of atherosclerosis, we find that SFK signalling regulates platelet‐dependent recruitment of monocytes. However, loss of a single SFK, Fgr or Lyn, reduced platelet‐mediated monocyte recruitment in vitro. This translated into a significant reduction in the burden of atherosclerotic disease in Fgr −/− /ApoE −/− or Lyn −/− /ApoE −/− animals. SFK signalling is not redundant in thrombo‐inflammatory vascular disease and individual SFK may represent targets for therapeutic intervention.